Magnetic resonance, a phenomenon with a great potential in medicine, but with a complex physical background – Part 3: The basic principles of magnetic resonance imaging - Bojan Božič; Luka Kristanc; Gregor Gomišček (Zdravniški Vestnik, 2014)
Two basic problems have to be solved when dealing with imaging techniques – the adequate image contrast and the spatial reconstruction of images. In this article, the basic concepts of solving these two problems in the case of magnetic resonance imaging (MRI) are shown. Based on the spin echo, three ways of contrast optimization, i.e., spin density, T1- and T2-weighted MRI, are dealt with more thoroughly. The use of contrast media is also discussed. Furthermore, we explain the basic method of spatial encoding in MRI, i.e., the determination of the location of tissue signal source with the use of magnetic field gradients (“the principle of frequency encoding”), and the use of the Fourier transform. Finally, the back-projection reconstruction technique is presented.